To the 140th anniversary of the birth of the founder of gerontology and geriatrics V.G. Korenchevsky - N. M. Zalutskaya; M. A. Akimenko (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2020)
.